Establishing a Model for the Deep Water Wave of Vietnam East Sea for Calculating Detailed Hydrodynamics in Coastal Area - Loc, Nguyen Xuan; Dinh Duc, Dang; Ngoc Anh, Tran; Thanh Tung, Tran (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 3DO - 10.25073/2588-1094/vnuees.4680, 2021)
This study tested the development of a wavefield simulation model for the East Sea area with good quality, replacing global data sources to be proactive in data sources in order to serve detailed hydrodynamic calculations for coastal areas. The model toolkit used is MIKE 21 FM, this is a widely used toolkit in the world thanks to its advantages such as user-friendliness, good computing support, and simulation of many hydrodynamic problems. The model has been calibrated and verified with data from typical oceanographic stations representing the three marine areas in Vietnam, Bach Long Vi, Con Co and Phu Quy, which have shown good results. Along with that, the study also evaluated the calculation results with the coastal wave data and also showed positive results. However, some periods have complicated movements, the model has not really been closely calculated.